The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/eap.2335
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA metabarcoding as a useful tool for evaluating terrestrial mammal diversity in tropical forests

Abstract: Innovative techniques, such as environmental DNA (eDNA) metabarcoding, are now promoting broader biodiversity monitoring at unprecedented scales, because of the reduction in time, presumably lower cost, and methodological efficiency. Our goal was to assess the efficiency of established inventory techniques (live‐trapping grids, pitfall traps, camera trapping, mist netting) as well as eDNA for detecting Amazonian mammals. For terrestrial small mammals, we used 32 live‐trapping grids based on Sherman and Tomahaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 72 publications
3
45
0
3
Order By: Relevance
“…In freshwater, terrestrial vertebrates can be detected through the DNA they leave when e.g. drinking or defecating [24][25][26][27][28] , and DNA from vertebrates can be detected in the gut contents of parasitic, scavenging or coprophagous invertebrates 13,[29][30][31][32] .…”
Section: Mainmentioning
confidence: 99%
“…In freshwater, terrestrial vertebrates can be detected through the DNA they leave when e.g. drinking or defecating [24][25][26][27][28] , and DNA from vertebrates can be detected in the gut contents of parasitic, scavenging or coprophagous invertebrates 13,[29][30][31][32] .…”
Section: Mainmentioning
confidence: 99%
“…As the field matures, considerable research effort now focuses on the "ecology of eDNA" (Barnes & Turner, 2016) quantifying and understanding factors influencing eDNA detections beyond inventories alone. Comparative studies have shown that metabarcoding of aquatic eDNA matches or even outperforms conventional methods of community sampling (Bessey et al, 2021;Mena et al, 2021;Ruppert et al, 2019). Additionally, an indication of terrestrial biodiversity can also be obtained from eDNA analysis of water and sediments sampled from aquatic systems (Sales et al, 2020;Ushio et al, 2017), though detections may be biased towards semi-aquatic species.…”
Section: Figures 1 Tomentioning
confidence: 99%
“…Additionally, an indication of terrestrial biodiversity can also be obtained from eDNA analysis of water and sediments sampled from aquatic systems (Sales et al, 2020;Ushio et al, 2017), though detections may be biased towards semi-aquatic species. A comparison of tropical mammal detection methods (Mena et al, 2021) including eDNA from lentic and lotic systems, live-trapping, pitfall traps, camera traps, and mistnets found integrated methods provide best estimates of community composition.…”
Section: Figures 1 Tomentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large range of possible TAS applications including variant detection and tumour profiling in cancer research, the detection of somatic mutations or those associated with susceptibility to disease, new findings in the field of phylogeny and taxonomy studies or the discovery of useful genes for applications in molecular breeding 2 , 3 , 9 , 10 . In the field of environmental sciences, TAS is becoming increasingly important, as it facilitates the assessment of the taxonomic composition of environmental samples with the help of metabarcoding approaches such as environmental DNA (eDNA) based biomonitoring or food web studies 11 13 .…”
Section: Introductionmentioning
confidence: 99%